2012
DOI: 10.15560/8.4.722
|View full text |Cite
|
Sign up to set email alerts
|

Check list of ground-dwelling ants (Hymenoptera: Formicidae) of the eastern Acre, Amazon, Brazil

Abstract: The ant fauna of state of Acre, Brazilian Amazon, is poorly known. The aim of this study was to compile the species sampled in different areas in the State of Acre. An inventory was carried out in pristine forest in the municipality of Xapuri. This list was complemented with the information of a previous inventory carried out in a forest fragment in the municipality of Senador Guiomard and with a list of species deposited at the Entomological Collection of National Institute of Amazonian Research– INPA. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 23 publications
2
12
0
2
Order By: Relevance
“…This richness is 5.40% of the species and 40.30% of the genera of the Neotropical Region; 14.10% and 53.36% of the species of the genera dwelling in Brazil, and 18.7% and 56.73% of the species of the genera of Amazon ( [58]. It is noteworthy that only named species are on the list presented here, and there are undergoing studies to show a realistic scenario of bioecological aspects involving these insects to maintain the balance of this natural system [59] (Table 5).…”
Section: Richness Abundance and Composition Of The Ant Fauna In Caximentioning
confidence: 97%
See 1 more Smart Citation
“…This richness is 5.40% of the species and 40.30% of the genera of the Neotropical Region; 14.10% and 53.36% of the species of the genera dwelling in Brazil, and 18.7% and 56.73% of the species of the genera of Amazon ( [58]. It is noteworthy that only named species are on the list presented here, and there are undergoing studies to show a realistic scenario of bioecological aspects involving these insects to maintain the balance of this natural system [59] (Table 5).…”
Section: Richness Abundance and Composition Of The Ant Fauna In Caximentioning
confidence: 97%
“…Strumigenys perparva (Brown, 1958) and Strumigenys elongata (Roger, 1863) are very common and abundant in leaf litter of primary forest in Caxiuanã; they are voracious predators, have long jaws, jump to catch the prey, and, like most species of this genus, feed on small invertebrates; they dwell in South America, and S elongata (Roger, 1863) also occurs in Central America [56]- [58] [61] [62].…”
Section: Richness Abundance and Composition Of The Ant Fauna In Caximentioning
confidence: 99%
“…In fact, few inventories have been conducted between the extremes of the G. vriesi occurrence (e.g. Souza et al, 2015;Miranda et al, 2012).…”
Section: Short Notementioning
confidence: 99%
“…Tropical forests represent only 7% of biomes of the planet, however, these ecosystems host more than half of all known species of plants and animals (Wilson 1988;May 2010;Miranda et al 2012). The Brazilian Amazon rainforest has one of the greatest biodiversities in the world, including the greatest diversity of social wasps (Silveira 2002;Somavilla et al 2014;Barbosa et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the existence of areas with a high biodiversity and high degree of endemism in this state (Souza et al 2003) for plants (Prance 1973;Silveira et al1997;Goldenberg and Meirelles 2011), mammals (Calouro 1999), birds (Haffer 1987;Whitaker and Oren 1999;Guilherme 2001;Guilherme and Borges 2011), amphibians (Lima et al2007), some insect orders (Brown 1991), including ants (Oliveira et al 2009;Miranda et al 2012), paper wasps (Morato 2001), lepidopterans (Brow, 1977, coleopterans (Vaz-de-Melo 1999), dipterans (Carvalho and Esposito 2010) and other arthropods, such as Opiliones (Villarreal-Manzanilla and Pinto-Da-Rocha 2006). Yet, very little is known about the diversity of social wasps in this part of the Amazon, since only two surveys carried out in Acre included social wasps (Richards 1978;Moratoet al2008).…”
Section: Introductionmentioning
confidence: 99%